Echinacea spp.: The cold-fighter herbal remedy? - Eleni Kakouri; Marjan Talebi; Petros A. Tarantilis (Elsevier, 2024)
Introduction: Echinacea spp. are worldwide known as anti-inflammatory medicinal plants. The phytochemistry of the genus Echinacea is complex, however most notable compounds to which the biological activity is attributed are the alkamides. Much research focuses on the study of certain Echinacea species, namely E. angustifolia, E. pallida, E. purpurea, and E. lannata, to deal with common cold symptoms, however, results between the various studies are inconsistent. There is a historical background for the therapeutic use of the plant against various disorders by many civilizations. Additionally, Echinacea species therapeutic uses in Traditional Chinese Medicine are discussed. Methodology: Databases including PubMed, Google Scholar and ScienceDirect were used for the research using the following keywords: Echinacea, anti-inflammatory, anti-viral, immunostimulatory, cold-fighter, chemistry, alkamides and Traditional Chinese Medicine. The purpose of this review paper is to discuss the existing findings regarding the immunostimulatory, anti-inflammatory, and anti-viral activities of Echinacea species. Results: Echinacea extracts contain a variety of secondary metabolites including caffeic acid, derivates of caffeic acid, flavonoids and alkamides. Alkamides, are the most studied compounds and the pharmacological activities of the plant are mainly attributed to those. Discussion: Data gathered from the in vitro and in vivo studies provide substantiation regarding the anti-inflammatory, immunomodulatory and anti-viral effects of Echinacea species. On the contrary evidence from clinical trials questions the useful effects of the plant in reducing the frequency and length of the common cold. Conclusion: Findings of the studies presented in the manuscript indicate that more research should be performed to evaluate whether Echinacea spp. is indeed a cold-fighter remedy. Additionally, conducting further studies regarding the bioavailability, pharmacokinetics, and toxicity of the plant is highly recommended.